Deformation and failure characteristics of Volcanic soil at landslides site due to the 2016 Kumamoto Earthquake - W. O. Sumartini; H. Hazarika; T. Kokusho; S. Ishibashi; D. Matsumoto; B. Chaudhary (Lowland Technology International, 2018)
A chain of earthquakes with a maximum moment magnitude of 7.3 MW struck Kumamoto prefecture and its vicinity from April 14-16th, 2016. It generated widespread landslides not only on steep slopes but also on gentle slopes. The landslides caused huge damages to nature, infrastructure, and loss of lives. Thus, it is crucial to determine the failure mechanism of those slopes which were formed by volcanic soil and to elucidate the effect of cyclic loading on strength characteristics of the soil. A series of investigations of the soil, which is orange colored, was conducted. Undrained static and cyclic triaxial tests were performed. Also, x-ray powder diffraction test, x-ray fluorescence test, and scanning electron microscope test were performed for further understanding of the material behavior. The triaxial test revealed semi dilative behavior under monotonic loading with small confining stress and contractive behavior on high confining stress. In the cyclic triaxial tests under in situ confining stress, cyclic mobility by lower cyclic stress and flow failure by higher cyclic stress was observed. Also, soil fabric, chemical composition, and mineral composition, which describe the deformation behavior and failure characteristics of the soil has been reported.